2015
DOI: 10.1177/0734282915607161
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Sense of School Belonging Across Cultural Contexts Using the PSSM

Abstract: Despite its popularity, the factorial structure of the Psychological Sense of School Membership (PSSM) Questionnaire remains controversial. The current study set out to clarify its structure across different cultural contexts. The study was carried out among 1,928 adolescents aged 11 to 20 years in the Netherlands, Kenya, Indonesia, and Spain. Item-based measurement models with a single factor did not show a good fit. A bifactor method (defining a method factor for negatively worded items) did not show a good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 23 publications
(28 reference statements)
1
31
0
3
Order By: Relevance
“…Three studies were conducted in the U.S. (Hagborg, 1994; O'farrell and Morrison, 2003; Ye and Wallace, 2014); two were conducted in China (Cheung and Hui, 2003; Cheung, 2004); one was conducted in Australia (You et al, 2011); one was conducted in Japan (Togari et al, 2011); and one was a multi-country (Netherland, Kenya, Indonesia, and Spain) comparison study (Abubakar et al, 2015). The latter study included a sample of 14- to 18-year old adolescents from Spain, but some of them responded to the PSSM scale in Spanish while others responded to the scale in Basque (the authors did not provide the exact proportion of respondents for each language) (Abubakar et al, 2015). There is some variability regarding the number of extracted factors that show a good fit, the items included in each factor and the total number of items to be included in the scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies were conducted in the U.S. (Hagborg, 1994; O'farrell and Morrison, 2003; Ye and Wallace, 2014); two were conducted in China (Cheung and Hui, 2003; Cheung, 2004); one was conducted in Australia (You et al, 2011); one was conducted in Japan (Togari et al, 2011); and one was a multi-country (Netherland, Kenya, Indonesia, and Spain) comparison study (Abubakar et al, 2015). The latter study included a sample of 14- to 18-year old adolescents from Spain, but some of them responded to the PSSM scale in Spanish while others responded to the scale in Basque (the authors did not provide the exact proportion of respondents for each language) (Abubakar et al, 2015). There is some variability regarding the number of extracted factors that show a good fit, the items included in each factor and the total number of items to be included in the scale.…”
Section: Introductionmentioning
confidence: 99%
“…For example, one study found that the school membership scale should include just 5 items from the original scale (O'farrell and Morrison, 2003). A different study found that a one-factor model showed a good fit, using all the items but combining items per target (e.g., school, teachers) (Abubakar et al, 2015). However, two latent factors appear in the Chinese version (Cheung and Hui, 2003; Cheung, 2004), and three factors in other studies (Hagborg, 1994; You et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…tarafından yapılan ölçeğin farklı kül-türlerdeki işlevselliğine yönelik meta-analiz sonuçlarına göre, bazı kültürlerde iki ve bazı kül-türlerde ise üç bileşeninin olduğu rapor edilmiştir. 14 (3,4,7,8,9,15,18) olup, faktör adı "algılanan kabul" olarak tanımlanmıştır. Bu alt ölçekte yer alan yedi maddenin faktör yükleri ,44-,72 arasın-dadır ve Cronbach Alfa iç tutarlılık katsayısı ,75'tir.…”
Section: Araştirma Modeli̇unclassified
“…Bu alt ölçekte yer alan yedi maddenin faktör yükleri ,44-,72 arasın-dadır ve Cronbach Alfa iç tutarlılık katsayısı ,75'tir. Üçüncü bileşene ait beş maddenin (2,5,10,11,14) faktör adı "algılanan değer" olarak düşünülmüştür. Bu alt ölçekte yer alan beş maddenin faktör yük-leri ,54-,66 arasındadır ve Cronbach Alfa iç tutarlı-lık katsayısı ,68'dir.…”
Section: Araştirma Modeli̇unclassified
See 1 more Smart Citation